Performance Analysis of Asset BMN Managers At The Head Office Ministry of Health os The Republic of Indonesia - Parikesit Mardianto (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
The management of assets BMN is a very important part of state finances (Law no.17 / 2003. The phenomenon shows the tendency that the quality of the performance of BMN asset managers in the office Ministry of Health Republic of Indonesia is strongly influenced by its human resources, so it is interesting to study more deeply, the extent of its influence. The aim of this research is to find out and analyze the effect of human resources competence, financial compensation and asset management on the performance of BMN asset managers at the Head Office of the Ministry of Health of the Republic of Indonesia. The sample of this research is the 120 BMN Asset Managers. While the data analysis uses PLS (Partial Least Square). The results showed that the acquisition of pvalues of 0.105> 0.05, it can be seen that the Human Resource competency variable does not have significant effect to the performance of BMN asset managers at the Ministry of Health Headquarters. Thus even though the asset manager has good Human Resource competencies, it has no significant effect or only has a small effect on improving the performance of the asset manager.The variable of financial compensation gets pvalues of 0.121> 0.05, so it can be seen that the variable of financial compensation does not have no significant effect the performance of BMN asset managers at the Ministry of Health Headquarters. Thus even though the asset manager is given a large and adequate financial compensation, it has no significant effect or only has a small effect on improving the performance of the asset manager. Asset management variable has a value of 0.023 <0.05, it can be seen that the asset management variable has a significant effect on the performance of BMN asset managers at the Ministry of Health Headquarters. Thus this value indicates that the better the implementation of asset management felt by the asset manager, the better the performance of the asset manager will be.Keywords: Human Resources Competency, Financial Compensation, Asset Management and Performance Abstrak:Pengelolaan aset BMN merupakan bagian yang sangat penting dalam keuangan negara (UU No.17 / 2003). Fenomena tersebut menunjukkan kecenderungan bahwa kualitas kinerja asset manager BMN di kantor Kementerian Kesehatan Republik Indonesia sangat dipengaruhi oleh sumber daya manusianya, sehingga menarik untuk dikaji lebih dalam, sejauh mana pengaruhnya. Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh kompetensi sumber daya manusia, kompensasi finansial dan manajemen aset terhadap kinerja pengelola aset BMN di Kantor Pusat Kementerian Kesehatan Republik Indonesia. Sampel dari penelitian ini adalah 120 Asset Manager BMN. Sedangkan analisis datanya menggunakan PLS (Partial Least Square). Hasil penelitian menunjukkan perolehan pvalues sebesar 0,105> 0,05 terlihat bahwa variabel kompetensi Sumber Daya Manusia tidak berpengaruh signifikan terhadap kinerja asset manager BMN di Kantor Pusat Kementerian Kesehatan. Dengan demikian meskipun Manajer Aset memiliki kompetensi Sumber Daya Manusia yang baik, namun tidak berpengaruh signifikan atau hanya berpengaruh kecil terhadap peningkatan kinerja manajer aset. Variabel kompensasi finansial mendapatkan nilai p 0,121> 0,05, sehingga dapat diketahui bahwa variabel kompensasi finansial tidak berpengaruh signifikan terhadap kinerja pengelola aset BMN di Kantor Pusat Kementerian Kesehatan. Dengan demikian meskipun pengelola aset diberikan kompensasi finansial yang besar dan memadai, namun tidak berpengaruh signifikan atau hanya berpengaruh kecil terhadap peningkatan kinerja pengelola aset. Variabel manajemen aset memiliki nilai 0,023 <0,05, terlihat bahwa variabel manajemen aset berpengaruh signifikan terhadap kinerja pengelola aset BMN di Kantor Pusat Kementerian Kesehatan. Dengan demikian nilai tersebut menunjukkan bahwa semakin baik implementasi manajemen aset yang dirasakan oleh pengelola aset maka akan semakin baik pula kinerja pengelola aset tersebut.Kata Kunci: Kompetensi Sumber Daya Manusia, Kompensasi Finansial, Manajemen Aset dan Kinerja